Prevalence and risk factors of bovine viral diarrhea in Colombian cattle - Diego Ortiz Ortega; Rodrigo Alfredo Martínez Sarmiento; Julio César Tobón Torreglosa; Juan Felipe Rocha (Veterinary World, 2020)
Background and Aim: Bovine viral diarrhea virus (BVDV) is present in most cattle-raising countries around the world, and it has a negative economic impact in cattle herds. In Colombia, previous studies have estimated the prevalence of BVDV in specific locations. The aim of this study was to estimate the prevalence of BVDV in cattle herds located at several municipalities across the country and to identify the associated risk and protective factors.